2013
DOI: 10.1111/jpc.12442
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and physical activity patterns in children and adolescents

Abstract: It is clear that activity levels are insufficient for all children, in particular overweight/obese children and adolescents, although the precise nature of the relationship appears to differ between boys and girls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
49
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 49 publications
(90 reference statements)
5
49
1
3
Order By: Relevance
“…Firstly, a better understanding of patterns of activity may be valuable information for designing successful interventions that target certain activity behaviors or times or days. 7,8 Secondly, detailed information can be used to assess adherence to key intervention messages, such as reducing prolonged bouts of sedentary time. Thirdly, recent literature has suggested that the absolute levels of activity may not be enough to explain differences in health outcomes, but particular patterns in behavior may be critical (including intensity and bout length).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Firstly, a better understanding of patterns of activity may be valuable information for designing successful interventions that target certain activity behaviors or times or days. 7,8 Secondly, detailed information can be used to assess adherence to key intervention messages, such as reducing prolonged bouts of sedentary time. Thirdly, recent literature has suggested that the absolute levels of activity may not be enough to explain differences in health outcomes, but particular patterns in behavior may be critical (including intensity and bout length).…”
Section: Introductionmentioning
confidence: 99%
“…A few previous studies have examined the differences in weekend versus school day behavior of obese and overweight children and adolescents. 7,13,14 Laguna et al found no differences in physical activity between weekdays and weekends for overweight or normal weight adolescents. 7 Conversely, Treuth et al found that both overweight and normal weight girls participated in less moderate-to-vigorous-physical-activity (MVPA) on the weekends compared to weekdays.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Germany, less than a fifth of school children between the ages of 7 and 10 years engage in sufficient MVPA [13,14]. Yet, these data are based on self-report, but even with objectively derived data, children hardly meet the WHO physical activity recommendations [15][16][17][18][19]. This has been shown to especially vary between gender and countries.…”
Section: Introductionmentioning
confidence: 99%